SrSnO3:Nd obtained by the polymeric precursor method - de Souza, Soraia Carvalho; Ferreira Alves, Mary Cristina; de Oliveira, A. Luiz M.; Longo, Elson [UNESP]; Gomes Vieira, F. Ticiano; Gomes, Rodinei Medeiros; Soledade, L. E. B.; de Souza, A. G.; Garcia dos Santos, Ieda M. (Springer, 2009)
In this work, the synthesis of Nd-doped SrSnO3 by the polymeric precursor method, with calcination between 250 and 700 A degrees C is reported. The powder precursors were characterized by TG/DTA and high temperature X-ray diffraction (HTXRD). After heat treatment, the material was characterized by XRD and infrared spectroscopy. Ester and carbonate amounts were strictly related to Nd-doping. According to XRD patterns, the orthorhombic perovskite was obtained at 700 A degrees C for SrSnO3 and SrSn0.99Nd0.01O3. For Sr0.99Nd0.01SnO3, the kinetics displayed an important hole in the crystallization process, as no peak was observed in HTXRD up to 700 A degrees C, while a XRD patterns showed a crystalline material after calcination at 250 A degrees C.
Keywords: Perovskite; Stannate; Neodymium-doping; Thermal analysis by TG/DTA; HTXRD